Tinjauan Yuridis Normatif terhadap Tindakan Pidana Bullying Dikalangan Pelajar - M.Raihan Rizqullah; Sabda Abdillah Lubis; Muhammad Ichsan Parinduri; Rahmat Surkhalid Nasution (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Bullying is actually an act of aggression that can be shown with verbal aggression or physical aggression. Verbal aggression is an attempt to hurt another party with the expression of words, speech, sentences that are sharp, harsh and tend to hurt the feelings of others. Verbal aggression can be said directly when dealing with one person with one person. The objectives that the researcher wants to achieve to answer the problems that will be studied in this study are: 1) Forms of bullying in schools. 2) Providing legal protection for children who are victims of bullying in schools. In this study, the researcher used normative legal research, normative legal research. The results of this study produced data showing that there are three forms of bullying, namely physical bullying, verbal bullying, and cyber bullying. Meanwhile, with the help of several parties, the legal protection that can be given to victims is preventive and repressive to prevent and overcome bullying in schools.